(untitled) (Ustozlar uchun, 2026)
The aorta is the largest and most important artery in the human body, forming the foundation of the entire systemic circulatory system. It originates from the left ventricle and performs the function of delivering oxygen-rich blood to the entire organism. A deep understanding of the anatomical structure and physiological functions of the aorta is of fundamental importance for the fields of cardiovascular medicine, surgery, and diagnostics. This literature review covers the embryology, anatomy, historical division, wall structure, physiological characteristics, and age-related changes of the aorta. The sources used were taken from modern scientific publications and medical manuals from 2019-2024.